Influence of polliniser position and honeybee colony distance in the set and quality of deciduous fruit in the Western Cape - Ramongalo, Boipelo Kgomotsego (Stellenbosch : Stellenbosch University, 2010)
Thesis (MSc)--Stellenbosch University, 2010.